Model-driven engineering and software development : second International Conference, MODELSWARD 2014, Lisbon, Portugal, January 7-9, 2014, Revised selected papers /: second International Conference, MODELSWARD 2014, Lisbon, Portugal, January 7-9, 2014, Revised selected papers. (2015) - Unknown
No abstract available